Litigância repetitiva: causas, técnicas processuais de julgamento e os limites do Processo Civil - Serpa, Luciane (2018)
Repetitive litigation is a complex large-scale phenomenon, which may involve the clarification of facts or be limited to a strictly legal dispute concerning the interpretation or enforcement of legal rules. Its main feature is the mass filing, at different times across different geographies, of identical lawsuits by people who have no legal relationship to each other. For this reason, it is impossible to bring all lawsuits together for judgment pursuant to the traditional civil procedures rules (joinder, third party intervention, connection, concurrence). Repetitive litigation originates in mass society, increased consumption, and new social and economic rights. In Brazil, the external cause of repetitive ligation was the 1988 Constitution and the tardy recognition of a range of rights. Investigating potential triggers is important to adequately understand the phenomenon and find solutions to mitigate the problem. Collective actions for homogeneous individual rights was the first procedural path coping with mass litigation and their main goal was creating a procedural avenue to increase access to justice. Collective actions are a legal procedural feature of the State of Social Welfare. Changes in the understanding of the role of the State and the Courts, coupled with the lack of effectiveness in solving serial disputes, have led them to a relative decline. At the same time, there are new procedural mechanisms that aim at achieving collective effects of decisions on individual actions, whose main objective becomes managing the public service provided by the Courts, through standardizing decision making (binding precedents). The 2015 Brazilian Code of Civil Procedure increased the procedural effects of repetitive case judgment techniques through the new rules on repetitive appeals to higher courts and the creation of the Repeated Demands Resolution (IRDR) under the jurisdiction of state and regional courts. The approximation between collective actions and judgment techniques by sampling is inevitable, notwithstanding the legal system being the first dividing line between the niches of collective and plurindiviudal rights protection. In the systems of norms, there is no hierarchy among the techniques, but said techniques are adapted to the case at issue and to the strategies of the parties and the Judiciary itself